EDUKASI TOILET TRAINING PADA IBU YANG MEMILIKI ANAK PRA SEKOLAH SEBAGAI UPAYA MENGEMBANGKAN PENGENDALIAN DIRI KEMAMPUAN ELIMINASI - Ferilia Adiesti; Nurun Ayati Khasanah (Jurnal Pengabdian Masyarakat, 2025)
Children who have been toilet trained are taught to put on their own pants after urinating or defecating and are trained to manage where they urinate or defecate. As part of their community service, the faculty and students of Majapahit School of Health Sciences conducted outreach activities for mothers in Wonosari Village through both in-person and online educational sessions held once a week over two months regarding toilet training for pregnant women. In addition to providing health clinics, education was also conducted offline and outside of regular activities. A total of 25 mothers participated in this activity, thereby increasing their knowledge. This activity is expected to enhance the mothers' knowledge and enable them to apply it in their daily lives at home